Parent-child interactions and objectively measured child physical activity: a cross-sectional study - Hyatt Raymond R; Goldberg Jeanne P; Hughes Sheryl O; Hennessy Erin; Economos Christina D (BMC, 2010)
Abstract Background Parents influence their children's behaviors directly through specific parenting practices and indirectly through their parenting style. Some practices such as logistical and emotional support have been shown to be positively associated with child physical activity (PA) levels, while for others (e.g. monitoring) the relationship is not clear. The objectives of this study were to determine the relationship between parent's PA-related practices, general parenting style, and children's PA level. Methods During the spring of 2007 a diverse group of 99 parent-child dyads (29% White, 49% Black, 22% Hispanic; 89% mothers) living in low-income rural areas of the US participated in a cross-sectional study. Using validated questionnaires, parents self-reported their parenting style (authoritative, authoritarian, permissive, and uninvolved) and activity-related parenting practices. Height and weight were measured for each dyad and parents reported demographic information. Child PA was measured objectively through accelerometers and expressed as absolute counts and minutes engaged in intensity-specific activity. Results Seventy-six children had valid accelerometer data. Children engaged in 113.4 ± 37.0 min. of moderate-vigorous physical activity (MVPA) per day. Children of permissive parents accumulated more minutes of MVPA than those of uninvolved parents (127.5 vs. 97.1, p < 0.05), while parents who provided above average levels of support had children who participated in more minutes of MVPA (114.2 vs. 98.3, p = 0.03). While controlling for known covariates, an uninvolved parenting style was the only parenting behavior associated with child physical activity. Parenting style moderated the association between two parenting practices - reinforcement and monitoring - and child physical activity. Specifically, post-hoc analyses revealed that for the permissive parenting style group, higher levels of parental reinforcement or monitoring were associated with higher levels of child physical activity. Conclusions This work extends the current literature by demonstrating the potential moderating role of parenting style on the relationship between activity-related parenting practices and children's objectively measured physical activity, while controlling for known covariates. Future studies in this area are warranted and, if confirmed, may help to identify the mechanism by which parents influence their child's physical activity behavior.